Human-computer interaction - Preece, Jenny, 1949- (Addison-Wesley Pub. Co, 1994)
Offering the most comprehensive account of the multidisciplinary field of HCI, this book illustrates the powerful benefits of a user-oriented approach to the design of modern computer systems. It balances the technical and cognitive issues required for understanding the subtle interplay between people and computers, particularly in emerging fields like multimedia, virtual environments and computer supported cooperative work (CSCW).